A Review on Soar Programming - , Nitin; Bhushan, Brij; Srinivasan, S (International Journal of Computer Sciences and Engineering, 2020)
he objective of this paper is to review on soar cognitive architecture‘s programming aspect.to create the intelligent agents for solving any artificial intelligence problem. we discusses the procedure with sequential steps in which soar execution cycle executes within soar programming .The purpose of this paper is to give a programmer‘s fundamental understanding of how a running Soar program works, with as little theoretical baggage as possible. This will involve stepping through a program‘s behaviour and describing what‘s happening, with special attention to the ―hidden‖ parts of Soar